Model Pemrosesan Informasi pada Intensitas Perilaku Hate Speech Pengguna Media Sosial - Fajriyah, Nidaan; Hudaniah, Hudaniah; Prasetyaningrum, Susanti (Faculty of Psychology, University of Muhammadiyah Malang, Indonesia, 2019)
The intensity of hate speech behavior is the level of one’s activities in showing negative evaluations as well as justifying and spreading hatred upon others. The rising number of cases of hate speech, bullying, racism, and so on in social media, made researchers interested in conducting research on how students’ strategies in processing information obtained on social media. This study aims to determine the intensity of hate speech behavior by social media users on the selection of information processing strategies or messages on social media. This research incorporates a descriptive quantitative research model. The subjects of this study amounted to 158 people age 19-25 years who were selected using the accidental sampling technique. The research instruments in the present study are the information processing scale and hate speech behavior scale. The results showed that social media users in this study tended to use heuristic processing types (61%), systematic (35%), and systematic-heuristic (3%) which demonstrate that most social media users tended to think simply about the content of any information in social media.